Du « clan divin des femmes amoureuses » à la « race maudite » : élaboration, représentations et discontinuités de l’identité lesbienne dans la trajectoire de Mireille Havet (1898-1932) - Emmanuelle Rétaillaud-Bajac (Genre, Sexualité et Société)
This paper aims to analyze the elaboration of and the gaps in the identity of the French lesbian writer Mireille Havet (1898-1932), at a time when a saphic scene took shape in fin-de-siecle Paris and the First World War led to the destabilization of gender. Mireille Havet came of age in the saphic and homosexual cultures of the Belle Époque and later embodied the flamboyant and troubling figure of the 1920’s flapper. Nonetheless, she was also marked by a very traditional religious education which eventually led her to denounce her own homosexuality as the source of all her problems. Through the study of her case, this paper nuances the prevailing view of the 1920’s as a time of liberation for all lesbians and points toward tensions between competing models for homosexual and lesbian identities in a key historical moment.